Severe Acute Kidney Injury with Necrotizing Glomerulonephritis After Piperacillin/Tazobactam Therapy in a Patient with Peritonitis: A Case Report and Literature Review - Youn-Sik Oh; Man-Hoon Han; Yong-Jin Kim; You Hyun Jeon; Hee-Yeon Jung; Ji-Young Choi; Jang-Hee Cho; Sun-Hee Park; Chan-Duck Kim; Yong-Lim Kim; Jeong-Hoon Lim (Diagnostics)
Piperacillin/tazobactam (PT), a widely utilized broad-spectrum antibiotic, has been associated with acute kidney injury (AKI). Although the precise mechanism remains uncertain, and most cases of PT-associated AKI are mild, this report describes a rare and severe complication of PT, which manifested as severe AKI with necrotizing glomerulonephritis requiring hemodialysis. A 42-year-old man was transferred to the nephrology clinic due to progressive deterioration of kidney function. Prior to the transfer, the patient had been diagnosed with appendicitis complicated by peritonitis and received intravenous PT for 8 days. Baseline kidney function was normal, but serum creatinine subsequently increased to 7.2 mg/dL. Hemodialysis was initiated to address metabolic acidosis and edema. Kidney biopsy revealed severe acute tubular injury and necrotizing glomerulonephritis. Steroid therapy was initiated based on the biopsy findings, and serum creatinine returned to normal levels after 4 weeks of treatment. This case demonstrates that severe AKI with necrotizing glomerulonephritis can occur after PT use. Prompt kidney biopsy and the timely initiation of immunosuppressive therapy are essential for a favorable outcome.